How to speak dolphin - Rorby, Ginny (Scholastic Press, 2015)
Since her mother died, twelve-year-old Lily has struggled to care for her severely autistic half-brother, Adam, in their Miami home, but she is frustrated and angry because her oncologist step-father, Don, expects her to devote her time to Adam, and is unwilling to admit that Adam needs professional help--but when Adam bonds with a young dolphin with cancer Lily is confronted with another dilemma: her family or the dolphin's freedom.